What are Qualitative Research Ethics? - Wiles, Rose (The 'What is?' Research Methods Series, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. There has been an increasing interest in research ethics over the last decade given the increasing ethical regulation of social research. 'Ethical literacy' encourages researchers to understand and engage with the ethical issues that emerge in the process of research. This book provides a short, succinct and accessible overview of the field, highlighting the key issues and everyday ethical dilemmas that researchers are likely to face in different contexts. Covering a range of methods, the book provides clear guidance for researchers on how to identify an approach that fits with their moral and intellectual framework. It explores ethical issues relating to 'traditional' research methods as well as to new and emerging methods and approaches - particularly visual and online methods.